Effects of using Peer Instruction (PI) on Youth and Adult Education (YAE): an experience in mathematics (Research, Society and Development, 2020)
This research, with an exploratory purpose, aims to quantitatively assess the effects of using Peer Instruction (PI) on the beliefs and attitudes of students of the first year of high school in Youth and Adult Education at Colégio Pedro II, Campus Centro / RJ, in relation to math classes. To this end, students received regular expository classes in the months of April, May and June 2019 and classes with the active PI methodology in the months of August, September, October and November of the same year, aiming to compare both. The data were collected in three different moments of the course, through a questionnaire containing a semantic differential scale, in order to assess the students' beliefs and attitudes when comparing the regular expository classes with the PI classes. Afterwards, these data were analyzed statistically, by hypothesis testing, using the Minitab 18 software. The results showed that the PI positively influenced the students' beliefs and attitudes and that they preferred active classes over regular expository classes. We concluded that the active PI learning methodology proved to be an important pedagogical tool, with the potential to create a motivating and collaborative environment in the classroom. However, the result of this experimental research must be corroborated by other researches on the topic.